Bonding Warehouse, St. Vincent St., Trinidad - (:unkn) unknown (Unknown, 2011)
The postcard shows the Port of Spain harbour and the warehouses which were used for the storage of goods.
Colour: Sepia; Style: Landscape; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Warehouses--Trinidad and Tobago; Harbors--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; Architecture--Trinidad and Tobago